ANALISIS PENGGUNAAN IMPLIKATUR PERCAKAPAN DALAM FILM DILAN: DIA ADALAH DILANKU TAHUN 1990 KARYA PIDI BAIQ KAJIAN PRAGMATIK - Santhi Duwi Juni Sukmawati; NI Luh Sukanadi; I Nyoman Adi Susrawan (Prodi Pendidikan Bahasa dan Sastra Indonesia FKIP Unmas Denpasar, 2021)
This study aims to describe and explain about (1) The form and purpose of the conversation that contained in the Dilan Film: Dia adalah Dilanku tahun 1990 by Pidi Baiq, (2), The specific criteria for conversational implications in the Dilan Film: Dia adalah Dilanku tahun 1990 by Pidi Baiq, (3) The factors that cause the emergence of conversational implicatures in the Dilan Film: Dia adalah Dilanku tahun 1990 by Pidi Baiq. The research used was a descriptive qualitative research method. The subject of this research is a film titled Dilan: Dia adalah Dilanku tahun 1990 by Pidi Baiq. The results of this study found that forms and intentions, specific criteria of implicature, conversation, and factors that attract attention, such as the forms and intentions of conversational implicatures, the special criteria of conversational implicatures, context-dependent can be canceled, can be calculated and cannot be released. sensitivity, and changes in the topic of conversation. The factors that underlying are the factors of closeness and intimacy, sensitivity, and changes in the topic of conversation.